Güncel Kadın Hastalıkları ve Doğum Çalışmaları VII (Bahar) - Şen, Ahmet Eren; Erol, Mustafa; Şafak, İhsan; Çevikoğlu Kıllı, Mürşide; Şafak, İhsan; Dal, Yusuf; Özdilek Kırçiçeği, Feden Kübra; Balkaş, Gülay; Akgör, Utku; Aykut, Serdar; Avan, Mesut (2024)
-